JALAN RAYA SEBAGAI ARENA PERTUNJUKKAN SOSIAL: STUDI ETNOFOTOGRAFI JALAN PAHLAWAN SEMARANG - Darmawan, Diaz Restu (Solidarity: Journal of Education, Society and Culture, 2012)
Pahlawan Street has unique existence in the heart of Semarang. This study tried to find the social meaning of Pahlawan Street by looking at three things: 1) the conditions of Pahlawan Street that trigger social activities in the street, 2) the forms of social activity that occurs in the street, and 3) the meaning that emerged based on the activity that occurs on Pahlawan Street as a social arena. The study uses ethnophotography, a method in visual anthropology that use visual symbols or signs in the photographs taken by the author as a source of data. The author trace the visual symbols or signs in the photograph to look for the social meanings. Ethnophotography gives new understanding to teach sensitivity to the photographer to grasp the cultural aspects of social reality. The results show that the physical condition of Pahlawan street, its sidewalks, decorative lights, and various important offices enables the emergence of various social activities in the street. The activities, performed by a variety of elements and groups of people who visit the street, raises various meanings that symbolize Pahlawan Street as an important social arena in Semarang.